ANALISIS SIKAP PEMIRSA TERHADAP IKLAN INTERNET SERVICE PROVIDER SMARTFREN DI TELEVISI - Prakoso, Wahyu Gigih (Manajemen Bisnis, 2013)
Wahyu Gigih PrakosoProgram Studi Manajemen FEB UMME-mail: Why_ki2denB@yahoo.co.idABSTRACTThe research objective was to analyse the attitude of internet advertising Smart-fren service provider.Respondents were students who had intended to watch television. Data were collected from studentsof Muhammadiyah University of Malang by using questionnaires. The sum of respondents were 100students who were selected by using accidental sampling method. Analysis technique used logisticregression analysis. The result of result show that the structure of the message and the format ofmessages significantly influence positively to attitudes. While the message content and frequency ofadvertising serving significant negative influence on attitudes.Keywords: message, message structure, format messages, ad frequency, attitude.